Unusual Presentation of Central Nervous System Cryptococcal Infection in an Immunocompetent Patient - Saigal, Gaurav; Post, M. Judith Donovan; Lolayekar, Sudha; Murtaza, Amir (American Journal of Neuroradiology, 2005)
Summary: The imaging findings of cryptococcosis affecting the brain in immunocompetent patients can be different from the more commonly described findings in immunocompromised patients. We report a case of an extremely unusual MR appearance of central nervous system cryptococcosis in a 49-year-old immunocompetent man.